Perceived Sources of Stress and Coping Strategies among Clinical Dental Students in Two Nigerian Universities (2016)
Background: Dentistry is perceived as a highly stressful profession and the dental school is often where the stress begins. Contemporary dental curricula require students to attain diverse proficiencies such as acquisition of theoretical knowledge, clinical competencies, skills acquisition and best practices which add up to stress. The objectives were to identify the sources of perceived stress, and the coping strategies adopted by clinical dental students in two Nigerian Universities. Materials & Methods: A cross-sectional study involving all clinical students in the two oldest dental schools in Nigeria. A validated self administered, structured questionnaire comprising of the modified version of dental environmental stress survey(DES), the perceived stress scale and brief coping scale was used in collecting data from the participants. Results: The potential sources of stress which were most frequently reported were the academic factors with volume of learning rated highest (84.2%) followed by demanding curriculum (72.6%) and frequent formative and summative assessment (51.7%). Inadequate infrastructures and erratic power supply were considered the most frequent(70.7%, 67.6%) sources of stress among the physical and environmental factors. Workload was also a major concern for stress with requirement to perform specified types and number of procedures rating the highest(76.9%) followed by time limits(69.8%). More (47.8%) females pray/ meditate while 29.6% cry as a means of relieving stress while the males play games which are all statistically significant (p= 0.003, 0.001 and 0.000 respectively). Conclusion: The most frequently reported source of stress are the academic factors with volume of learning rated the highest followed by demanding curriculum and frequent examinations. The strategies adopted to cope with stress across the gender were praying and crying among females and playing games in males